2018
DOI: 10.2741/4624
|View full text |Cite
|
Sign up to set email alerts
|

Natural aging as as a sequential poly-systemic syndrome

Abstract: We review the progression of aging as a sequential development of multiple syndromes analogous to other diseases. This generalized approach may allow practicing physicians to consider the signs of aging as manifestations of a poly-syndrome disease and facilitate prevention, diagnosis and treatment of common aging-related dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Aging is a multidimensional phenomenon that includes physiological, psychosocial, and biological changes (5). Aging is defined as a continuous process under cumulative, progressive, intrinsic, and deleterious factors (6,7). Frailty is an important concept in the science of aging and a very common aging syndrome (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is a multidimensional phenomenon that includes physiological, psychosocial, and biological changes (5). Aging is defined as a continuous process under cumulative, progressive, intrinsic, and deleterious factors (6,7). Frailty is an important concept in the science of aging and a very common aging syndrome (8).…”
Section: Introductionmentioning
confidence: 99%
“… 5 ) Aging is defined as a continuous process under cumulative, progressive, intrinsic, and deleterious factors. 6 , 7 ) Frailty is an important concept in the science of aging and a very common aging syndrome. 8 ) Frailty is defined as a state of increased vulnerability due to reduced physiological reserves and function in different organ systems when exposed to stress in individuals of the same chronological age.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have suggested that the aging process is affected by environmental [2, 3], nutritional [4], and genetic factors [5] and have attempted to explore the mechanisms of aging. In addition, in modern times, an increasing number of aging-related diseases, such as cancer, cardiovascular disease, chronic degenerative diseases and other aging-related dysfunctions, have threatened human health [6, 7]. Even though increasing evidence has demonstrated that pharmacological intervention may delay the senescence process [8, 9], a definitely effective antiaging treatment has not yet been found since the mechanisms of aging are complicated.…”
Section: Introductionmentioning
confidence: 99%
“…In modern times, an increasing number of age-related diseases, such as chronic degenerative diseases and other aging-related dysfunctions, have threatened human health (Gladyshev and Gladyshev 2016; Krut’ko et al 2018). Contrary to mainstream modern medicine, TCM aims to interfere with the aging process as early as possible, thus preventing and delaying the occurrence and development of age-related diseases; this approach has begun to attract increasing attention from researchers (Liang and Yin 2010; Chen 2015).…”
Section: Discussionmentioning
confidence: 99%